1991
DOI: 10.1111/j.1365-2125.1991.tb03886.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous apomorphine increases regional cerebral blood flow in parkinsonian patients via peripheral mechanisms.

Abstract: 1. We have measured regional cerebral blood flow (rCBF) and motor function before and after the subcutaneous (s.c.) injection of apomorphine in parkinsonian patients deprived of their usual treatment for at least 48 h. 2. Nineteen patients, pretreated with domperidone (20 mg three times daily for 48 h), received a mean dose of 5.8 mg s.c. apomorphine. All patients switched 'on'. The mean motor score was significantly improved (‐65%, P less than 0.01) but no significant change in rCBF was observed. 3. Seven oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
(63 reference statements)
0
13
0
1
Order By: Relevance
“…Sabatini and colleagues [29], using xenon 133 washout and single-photon emission computed tomography (SPECT), studied a group of apomorphine-naive patients in contrast to our chronically exposed subjects. They found that apomorphine significantly increased global CBF.…”
Section: Apomorphine Effect On Global Cerebral Blood Flowmentioning
confidence: 98%
“…Sabatini and colleagues [29], using xenon 133 washout and single-photon emission computed tomography (SPECT), studied a group of apomorphine-naive patients in contrast to our chronically exposed subjects. They found that apomorphine significantly increased global CBF.…”
Section: Apomorphine Effect On Global Cerebral Blood Flowmentioning
confidence: 98%
“…rCBF remains proportional to regional cerebral metabolic rate (rCMR) under various conditions (McCulloch et al, 1982a;Beck et al, 1986;Tuor et al, 1986); thus, quantitative images of rCBF only need to be scaled to reflect rCMR. Dopaminergics usually do not affect the global CBF/CMR ratio (Berntman et al, 1976(Berntman et al, , 1978McCulloch and Harper, 1977;McCulloch et al, 1978McCulloch et al, , 1982aMcCulloch and Edvinsson, 1980;Azuma et al, 1988;Sharkey et al, 1991), but certain drugs can change it (Ingvar et al, 1983;Leenders et al, 1985;Tuor et al, 1986;Beck et al, 1988;Sabatini et al, 1991). This raises the question of whether U91356a alters the vasculature to decrease global CBF or whether it decreases neuronal activity in large areas of brain.…”
Section: Discussionmentioning
confidence: 98%
“…Also, in our study domperidone did not prevent the global fall in CBF. Domperidone does not affect central metabolism (Palacios and Wiederhold, 1987), but can block a disproportionate, presumably vascular, change in rCBF after apomorphine (Sabatini et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, activation CBF studies may demonstrate functional abnormalities which are undetectable under resting conditions (Di Piero et al 1990) and show cerebral areas rsponsible for vicariant functions after the primary circuit is destroyed (Chollet et al 1991), as well as shed light on the effects of drugs on specific brain functions (Sabatini et al 1991).…”
Section: Introductionmentioning
confidence: 99%